UJI EFEKTIFITAS EKSTRAK DAUN PANDAN WANGI (Pandanus amaryllifolius Roxb) TERHADAP PERTUMBUHAN BAKTERI Streptococcus mutans - Siti Juariah; Junia Wiranda; Harni Sepryani (Journal of Indonesian Medical Laboratory and Science, 2022)
Fragrant pandan leaves (Pandanus amaryllifolius Roxb) is a type of plant that contains flavonoid compounds, alkaloids, saponins and tannins that can function as antibacterial. Streptococcus mutans is one of the bacteria that causes dental caries. Fragrant pandan leaf extract is expected to be an alternative to overcome bacterial infections such as dental caries. Dental caries is a disease caused by damage to the enamel layer that can extend to the nerves of the teeth so that it will cause cavities caused by the bacterium Streptococcus mutans. The aim of this study was to determine the effectiveness of fragrant pandan leaf extract against the growth of Streptococcus mutans bacteria that causes dental caries. This type of research is a laboratory experiment using the disc diffusion method. Fragrant pandan leaves were extracted by maceration method using 96% ethanol as solvent. The results of this study showed that the pandan fragrant leaf extract had an inhibitory effect on the growth of Streptococcus mutans bacteria at concentrations of 25%, 50%, and 75% with an average inhibition zone diameter of 10.3 mm, 13.3 mm, 17.6. mm. Positive control (amoxicilin) ??44.3 mm and negative control (aquadest) had no value to inhibit bacterial growth. The conclusion is that pandan leaves extract (Pandanus amaryllifolius Roxb) can inhibit Streptococcus mutans which is the bacteria that causes dental caries.